2019
DOI: 10.1186/s42466-019-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

An omics-based strategy using coenzyme Q10 in patients with Parkinson’s disease: concept evaluation in a double-blind randomized placebo-controlled parallel group trial

Abstract: Background: This study focuses on genetically stratified subgroups of Parkinson's disease patients (PD) with an enrichment of risk variants in mitochondrial genes,who might benefit from treatment with the "mitochondrial enhancer" coenzyme Q10 (156 mg coenzyme Q10/d [QuinoMit Q10® Fluid] over six months). The study will be performed in a double-blind, randomized, and placebo-controlled parallel group manner.Methods: PD patients will be specifically identified and assigned to treatment groups stratified by their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Strategies to improve mitochondrial function have been under consideration for the treatment of neurological and psychiatric disorders for quite some time, with limited success in clinical trials [ 271 , 272 , 273 , 274 , 275 ], despite promising results in animal models [ 276 , 277 , 278 , 279 , 280 , 281 ]. Even in individuals with genetic mutations that cause mitochondrial dysfunction and multi-organ disease, there are few treatment options [ 282 ].…”
Section: Viable Avenues For Drug Discovery and Therapeutic Intervementioning
confidence: 99%
“…Strategies to improve mitochondrial function have been under consideration for the treatment of neurological and psychiatric disorders for quite some time, with limited success in clinical trials [ 271 , 272 , 273 , 274 , 275 ], despite promising results in animal models [ 276 , 277 , 278 , 279 , 280 , 281 ]. Even in individuals with genetic mutations that cause mitochondrial dysfunction and multi-organ disease, there are few treatment options [ 282 ].…”
Section: Viable Avenues For Drug Discovery and Therapeutic Intervementioning
confidence: 99%
“…After that, a more extensive study was performed with early PD-diagnosed patients, who were treated with doses up to 1200 mg per day, showing that CoQ10 was safe and well-tolerated and delayed the progressive function deterioration [ 69 ]. From these studies, doses and number of patients have been modified; however, the effects of preclinical trials have not been reproduced [ 70 , 71 , 72 , 73 ].…”
Section: Mitochondria-targeted Antioxidants Therapeutic Effect Onmentioning
confidence: 99%
“…Studies in flies identified vitamin k2 as an alternative electron carrier molecule that similar to ubiquinone can stimulate the ETC resulting in a rescue of Pink1-related phenotypes [ 27 ], nominating it to be a promising therapeutic strategy in the treatment of PINK1-related PD patients. The application of ubiquinone and vitamin k2 as therapy in patients has been initiated in clinical trials [ 98 , 99 ] and serves as an excellent example of therapeutic targets identified in flies that are now being tested in patients.…”
Section: The Mitochondrial-pd Connection In Drosophila Mmentioning
confidence: 99%